Spatial-Temporal Variability of Chlorophyll-a Concentration in Cenderawasih Bay and Surrounding Waters - Alianto Alianto; Baigo Hamuna (Journal of Applied Geospatial Information, 2020)
Chlorophyll-a is one of the parameters determining the primary productivity of water. In the fisheries sector, information on chlorophyll-a concentration in marine waters is very important for the prediction of fishing grounds. This study aims to analyze the variability of chlorophyll-a concentrations in Cenderawasih Bay and the surrounding waters, both spatial and temporal variability. Data from the Aqua-MODIS Level 3 monthly composite period from January to December 2019 was used to determine the concentration of chlorophyll-a. Time-series data are used to determine fluctuations of chlorophyll-a concentrations, while interpolation with the kriging method is used to determine the spatial distribution of chlorophyll-a. The analysis showed that the monthly average value of chlorophyll-a concentration in the study area ranged from 0.1988 – 0.3415 mg.m-3. The average value of chlorophyll-a concentration increases from March to June and then decreases in July or August. The highest average chlorophyll-a concentration was in March and the lowest in January. The maximum chlorophyll-a concentration in April and the minimum in August, which is around 9.1089 mg.m-3 and 0.0975 mg.m-3, respectively. The concentration of chlorophyll-a in Cenderawasih Bay and its surrounding waters is dominated by a low concentration, which ranges 0.1482 – 0.3158 mg.m-3. Generally, the variability of chlorophyll-a concentrations in the study area is influenced by seasons. The average chlorophyll-a concentration is high in the Transition I (West-east) and East seasons and will decrease in Transition II (East-West) until the West season. Spatially, chlorophyll-a concentrations in coastal areas are higher than in offshore waters. High chlorophyll-a concentrations are found around the border between Nabire Regency and Waropen Regency. The amount of run-off flow that supplies nutrients from the mainland greatly affects the high concentration of chlorophyll-a in the coastal area.